2020
DOI: 10.1101/2020.03.02.955757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversification of molecularly defined myenteric neuron classes revealed by single cell RNA-sequencing

Abstract: Autonomous functions of the gastrointestinal tract require the combined activity of functionally distinct neurons of the enteric nervous system (ENS). However, the range of enteric neuron diversity and how it emerges during development remain largely unknown.We here make a novel molecular definition of 12 enteric neuron classes (ENCs) within the myenteric plexus of the mouse small intestine. We identify communication features and provide histochemical markers for discrete motor, sensory, and interneurons toget… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
85
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(100 citation statements)
references
References 58 publications
15
85
0
Order By: Relevance
“…Analysis of IPANs is of critical interest given the prominent role played by this subtype in the ENS. Our findings confirm the existence of multiple IPAN subtypes previously indicated for mice 6,10 and expand the marker toolkit available to localize While stem cell transplantation studies have successfully generated ENs that integrate into aganglionic bowel 21,22 , it has not been possible to assess whether integrated cells accurately reflected adult EN subtypes. Our profiling of adult EN provides the first benchmark resource of its kind that can be used to assess whether EN generated by directed differentiation mimic their in vivo counterparts.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Analysis of IPANs is of critical interest given the prominent role played by this subtype in the ENS. Our findings confirm the existence of multiple IPAN subtypes previously indicated for mice 6,10 and expand the marker toolkit available to localize While stem cell transplantation studies have successfully generated ENs that integrate into aganglionic bowel 21,22 , it has not been possible to assess whether integrated cells accurately reflected adult EN subtypes. Our profiling of adult EN provides the first benchmark resource of its kind that can be used to assess whether EN generated by directed differentiation mimic their in vivo counterparts.…”
Section: Discussionsupporting
confidence: 80%
“…Among rodents, Nmu is known to label guinea pig IPANs and a recent study has confirmed this in mice based on co-localization with the established IPAN marker Calb2 6,10 . Our finding of Nmu in mouse IPANs is consistent with these studies, although to our knowledge NMU has been untested in the human ENS.…”
Section: Nmu and Klhl1 Mark Ipans In Mice While In Humans Only Nmu mentioning
confidence: 89%
See 2 more Smart Citations
“…Prior scRNAseq analysis of postnatal ENS did not detect and characterize the true identity of the MEN lineage. This is because previous studies were performed either exclusively on neural crest-derived ENS cells (Zeisel et al, 2018), or when done in a more agnostic manner, only applied known canonical neural markers to identify the ENS population (Drokhlyansky et al, 2019;Morarach et al, 2020). In either case, the discovery of the distinct identity and derivation of MENs would not have been possible.…”
Section: A Shift In the Balance Between The Two Lineages In The Adultmentioning
confidence: 99%